Diagnosis and Management of Macular Holes Traumatic - Reny Violeta; AK Ansyori; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2019)
Introduction. Macular hole is a defect in the retina involving the macula and fovea, in the form of damage to full thickness from the internal limiting membrane (ILM) to the outermost part of the photoreceptor layer . It was more often found in women. In patients with myopia disorders can be found at a younger age. In this case we report the macular hole caused by blunt trauma, as was the first time a macular hole case was discovered. Case Presentation. A man 24-year-old, Mr. C, came to Palembang RSMH eye clinic on August 15, 2014 with complaints of blurred right eye vision. Main Complaints: Right eye blurred. History Disease: Right eye blurred for about 3 months before entering the hospital. Blur is felt after the patient had a motorcycle accident 3 months ago. At that time the collision sufferer avoided the truck, the right eye hit the motorcycle handlebar, the patient then fell from the motorcycle and hit the highway head. A history of frequent headaches is denied, nausea, vomiting is denied, history of seeing in tunnels is denied. Supporting examination is Amsler Grid Oculi Dextra: there is a black hole in the middle of the image. differential diagnosis is Traumatic Macular Hole OD, Lamellar Macular Hole OD, work diagnosis is Traumatic Macular Hole stage 3 OD. Conclusion. Traumatic macular holes can occur immediately after blunt trauma to the eyeball, the accuracy of the diagnosis and the speed of the timing for surgery, greatly determining the prognosis. Vitrectomy and combined with internal limiting membrane peeling have been shown to provide excellent results in macular surgery in macular hole cases.